2007
DOI: 10.1083/jcb.20070310920070924c
|View full text |Cite
|
Sign up to set email alerts
|

New Tetrahymena basal body protein components identify basal body domain structure

Abstract: Due to a printing error, Fig. 4 appeared as a grayscale image. It appears in color in the online version and has been reprinted in color below. Figure 4. New T. thermophila basal body components were shown to localize to discrete structural domains. Protein localizations were assigned to specifi c domains if at least 20% of all gold particles in the immunoelectron microscopy compilation images are associated with the region. New protein components are listed in Fig. 2 B and in Figs. S1-3 (available at http://w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 0 publications
4
50
0
1
Order By: Relevance
“…Although mutant and biochemical analyses of individual proteins have been hugely important to our understanding of the cilium, the recent application of proteomic methods to the study of cilia has allowed catalogs of ciliary proteins to be compared between species and at great evolutionary distance (Keller et al, 2005(Keller et al, , 2006Pazour et al, 2005;Broadhead et al, 2006;Kilburn et al, 2007). Direct comparison between these ciliomes can identify proteins shared between sets, but can also be used to test whether ciliary proteins from one organism are encoded in the genome of another.…”
Section: Diversity Of Ciliomesmentioning
confidence: 99%
“…Although mutant and biochemical analyses of individual proteins have been hugely important to our understanding of the cilium, the recent application of proteomic methods to the study of cilia has allowed catalogs of ciliary proteins to be compared between species and at great evolutionary distance (Keller et al, 2005(Keller et al, , 2006Pazour et al, 2005;Broadhead et al, 2006;Kilburn et al, 2007). Direct comparison between these ciliomes can identify proteins shared between sets, but can also be used to test whether ciliary proteins from one organism are encoded in the genome of another.…”
Section: Diversity Of Ciliomesmentioning
confidence: 99%
“…Indeed, the appearance of "stubs" or sheaths of material remaining after cage isolation may illustrate the location of one or more of these proteins; these residual sheaths retain the ninefold symmetry of the basal body. Numerous kinetosome-associated proteins in the cortex of various ciliates have been described (Fleury et al 1998;Honts and Williams 2003;Jerka-Dziadosz et al 2001;Keryer et al 1990;Kilburn et al 2007;Lemullois et al 2004;Pearson and Winey 2009;Williams 1986). The residual structures we see may represent one of these proteins performing this linking role.…”
mentioning
confidence: 65%
“…The elements linking the cirral and membranellar basal bodies into polykinetids, and in turn cementing these organelles into the surrounding cortical architecture, have been poorly understood components of the pellicle. Even in recent reviews of basal-body structure and components, the protein composition of polykinetid basal-body linkers is scarcely addressed (Kilburn et al 2007;Pearson and Winey 2009). The present study has provided a better understanding of the structural basis for such linkage, and has identified a major protein component of these important interkinetosomal links.…”
Section: Kloetzel and Brann-basal-body Cages In Euplotesmentioning
confidence: 99%
See 1 more Smart Citation
“…Basal body proteins. Two gel bands (23a,b) produced a single gene identification, recently described as FTT18, a component of the basal body proteome (Kilburn et al 2007). Although ultrastructural analysis has revealed that the exchange junction itself is relatively clear of basal bodies, it is surrounded by membrane that is rich in them, and these could easily become involved in the isolation procedure.…”
mentioning
confidence: 99%